2007
DOI: 10.1007/s00404-007-0469-3
|View full text |Cite
|
Sign up to set email alerts
|

Patients with presenting unusual manifestations with gestational trophoblastic neoplasm: case series and review of literatures

Abstract: Early recognition of gestational trophoblastic neoplasms (GTN) will maximize the chances of cure with chemotherapy but some patients present with many different symptoms months or even years after the causative pregnancy making diagnosis difficult. Clinicians should be aware of the possibility of GTN in any reproductive age woman with bizarre central nervous system symptoms, gastrointestinal symptoms or radiographic evidence of metastatic tumor of unknown primary origin. We reported two cases of metastatic ges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Thirdly, the intra-uterine lesion may have penetrated the myometrium and reached the uterine serosa. The possibility of intra-abdominal bleeding caused by penetration of the myometrium by GTN and an actual case of myometrial penetration by a lesion have been reported previously (8). However, this could not be pathologically investigated in our patient since the uterus was not excised.…”
Section: Discussionmentioning
confidence: 72%
“…Thirdly, the intra-uterine lesion may have penetrated the myometrium and reached the uterine serosa. The possibility of intra-abdominal bleeding caused by penetration of the myometrium by GTN and an actual case of myometrial penetration by a lesion have been reported previously (8). However, this could not be pathologically investigated in our patient since the uterus was not excised.…”
Section: Discussionmentioning
confidence: 72%
“…As a rare and aggressive form of GTN [1], approximately 50% of GC cases develop from complete hydatidiform moles, 25% develop following miscarriage or ectopic pregnancy, and 25% develop after full-term pregnancy [8]. Approximately 80% of GTNs feature metastatic lesions in the lungs (80%), vagina (30%), pelvis (20%), liver (10%), and brain (10%) [9], with splenic metastasis incidence below 5% [4]. These highly vascular tumors are prone to aneurysms [5].…”
Section: Discussionmentioning
confidence: 99%
“…Gestational choriocarcinoma (GC), a malignant gestational trophoblastic neoplasm (GTN) representing a trimorphic proliferation of intermediate trophoblastic cells, syncytiotrophoblasts, and cytotrophoblasts [1], has an incidence of approxi-mately 1 in 50,000 pregnancies [2]. GC can metastasize to the brain, lungs, liver, kidney, and vagina [3], but splenic metastasis represents fewer than 5% of cases [4]. GTNs are highly vascular, and severe spontaneous hemorrhage can occur in response to tumor biopsy [1].…”
Section: Introductionmentioning
confidence: 99%
“…Many cases of successful pregnancy and delivery after uterine resection and reconstruction have been possible; however, uterine perforation after localized uterine resection has been reported [3,4]. Pregnancy in these patients is high risk owing to possible uterine rupture caused by uterine scars.…”
mentioning
confidence: 99%
“…Postpartum sexual abstinence may last up to 30 months among women in Sub-Saharan Africa [1][2][3]. In areas of high HIV prevalence, HIV-positive mothers who do not breastfeed are at higher risk of an earlier return of fertility compared with mothers who practice exclusive breastfeeding [4]. Little is known about the impact of HIV on sexual practices and use of contraception in the postpartum period.…”
mentioning
confidence: 99%